Comparative Analysis of Traditional and Fuzzy TOPSIS Methods in Satellite Telecommunication Market Entry Decisions - Nazarov, A.V. (Herald of Azerbaijan Engineering Academy, 2025)
This study compares traditional and fuzzy TOPSIS methods for decision-making in the satellite telecommunication market. Developed by Hwang and Yoon in 1981, TOPSIS selects the alternative closest to the ideal solution and farthest from the negative-ideal solution. The traditional method uses six criteria relevant to the satellite service market. Fuzzy TOPSIS extends this by incorporating fuzzy logic to handle uncertainty, using triangular fuzzy numbers for performance measures. The study outlines both methods' steps and their application in ranking alternatives. Results show that fuzzy TOPSIS provides a more nuanced analysis by accounting for uncertainties, enhancing decision-making quality.